Blood flow dynamics in the ascending aorta of patients with bicuspid aortic valve before and after transcatheter aortic valve replacement: a computational fluid dynamics study - Kang An; Fengwen Zhang; Wenbin Ouyang; Xiangbin Pan (BMC Cardiovascular Disorders, 2024)
Abstract Background Abnormal blood flow patterns are known to contribute to the ascending aortic dilation in patients with bicuspid aortic valve (BAV). The present study elucidated the blood flow characteristics in the dilated ascending aorta before and after transcatheter aortic valve replacement (TAVR) using computational fluid dynamics (CFD) analysis. Methods We performed CFD analysis in three BAV patients with ascending aortic dilation (maximum diameter ≥ 45 mm) who underwent TAVR. The blood flow streamline was visualized to evaluate the pre- and post-operative flow velocity, severity of vortex and helix, and wall shear stress (WSS) in the ascending aorta. Results Before the procedure, all three patients showed abnormal blood flow patterns, with vortex and helix in the ascending aorta. Regionally elevated WSS was also observed in the lateral or posterior ascending aortic wall (16.7 Pa, 12.2 Pa, and 14.5 Pa in patient 1, 2, and 3, respectively). After the procedure, the blood flow patterns significantly improved, and the maximum WSS also decreased (4.2 Pa, 1.1 Pa, and 3.2 Pa in patient 1, 2, and 3, respectively). Conclusion Abnormal blood flow patterns and WSS appeared to improve after TAVR in BAV patients with ascending aortic dilation. The impact on the long-term aortic growth rate and the incidence of aortic dissection requires further studies. Trial Registration Changes of Ascending Aortic Diameter in Patients Undergoing Transcatheter Aortic Valve Replacement. ClinicalTrial.gov number NCT05739253. Trial registration date 20,230,212.